2019
DOI: 10.1111/evo.13740
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary costs and benefits of infection with diverse strains of Spiroplasma in pea aphids*

Abstract: The heritable endosymbiont Spiroplasma infects many insects and has repeatedly evolved the ability to protect its hosts against different parasites. Defenses do not come for free to the host, and theory predicts that more costly symbionts need to provide stronger benefits to persist in host populations. We investigated the costs and benefits of Spiroplasma infections in pea aphids (Acyrthosiphon pisum), testing 12 bacterial strains from three different clades. Virtually all strains decreased aphid lifespan and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 96 publications
(188 reference statements)
1
33
0
Order By: Relevance
“…One possibility is the mechanisms have evolved independently and cannot transfer between species. Although parasitoid protection by H. defensa [45] is provided by a toxin-encoding bacteriophage (APSE) [46][47][48], and these phage also occur in the symbiont Arsenophonus [49] Spiroplasma is a costly symbiont in pea aphids: it shortens lifespan and reduces life-time reproduction [25]. Five of the strains considered in this study were examined for potential costs in a previous study [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is the mechanisms have evolved independently and cannot transfer between species. Although parasitoid protection by H. defensa [45] is provided by a toxin-encoding bacteriophage (APSE) [46][47][48], and these phage also occur in the symbiont Arsenophonus [49] Spiroplasma is a costly symbiont in pea aphids: it shortens lifespan and reduces life-time reproduction [25]. Five of the strains considered in this study were examined for potential costs in a previous study [25].…”
Section: Discussionmentioning
confidence: 99%
“…Although parasitoid protection by H. defensa [45] is provided by a toxin-encoding bacteriophage (APSE) [46][47][48], and these phage also occur in the symbiont Arsenophonus [49] Spiroplasma is a costly symbiont in pea aphids: it shortens lifespan and reduces life-time reproduction [25]. Five of the strains considered in this study were examined for potential costs in a previous study [25]. The symbionts in that study were in a different aphid genetic host background from either of those used here, so we are cautious about comparing the results too closely, but the patterns observed in that study (both Sp227 and Sp161 were found to have a greater reproductive cost and to be associated with higher mean reproductive age than strains Sp322, Sp327 and Sp709) do not imply that previously reported fitness costs correlate (positively or negatively) with either fungal or parasitoid resistance as reported in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…; Sakurai et al, 2005), reduced fecundity ( Spiroplasma sp., H. defensa , and S . symbiotica ; Chen et al (2000); Castañeda et al (2010); Li et al (2018); Mathé-Hubert et al (2019)), shorter aphid longevity ( Spiroplasma sp. and S .…”
Section: Introductionmentioning
confidence: 99%
“…and S . symbiotica ; Chen et al (2000); Mathé-Hubert et al (2019)), lower adult mass ( S . symbiotica; Skaljac et al (2018)), and increased susceptibility to insecticide ( S .…”
Section: Introductionmentioning
confidence: 99%
“…In this issue, Mathé‐Hubert et al. () used pea aphids ( Acyrthosiphon pisum ) as hosts to investigate the fitness costs of 12 endosymbiotic strains of Spiroplasma and one strain of Regiella insecticola and quantify their effects on parasitism by a species of parasitic wasp ( Aphidius ervi ). The authors assessed four different life‐history traits including intrinsic growth rate and lifetime reproduction, and found that each strain of Spiroplasma reduced overall host fitness with no strain expressing positive fitness effects in any variable compared to controls.…”
mentioning
confidence: 99%